2017
DOI: 10.1007/s10753-017-0551-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Macrophage Functions in Middle-Aged Rats: Relevance of Estradiol Level and Macrophage Estrogen Receptor Expression

Abstract: The aim of this study was to examine the influence of sex on age-related changes in phenotype and functional capacity of rat macrophages. The potential role of estradiol as a contributing factor to a sex difference in macrophage function with age was also examined. Thioglycollate-elicited peritoneal macrophages derived from the young (2 months old) and the naturally senescent intact middle-aged (16 months old) male and female rats were tested for cytokine secretion and antimicrobial activity (NO and HO product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Many cell types increase protein secretion with senescence 43 45 , a process associated with aging, as well as some repair processes 14 , 46 . Whereas we found some proteins secreted at higher levels in older macrophages, interestingly there were far more proteins secreted at higher levels in young cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cell types increase protein secretion with senescence 43 45 , a process associated with aging, as well as some repair processes 14 , 46 . Whereas we found some proteins secreted at higher levels in older macrophages, interestingly there were far more proteins secreted at higher levels in young cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we found some proteins secreted at higher levels in older macrophages, interestingly there were far more proteins secreted at higher levels in young cells. Whereas there is little information available on the effect of aging on macrophage cell secretion, a few studies examining secretion of individual proteins with age, also found lower levels of protein secretion of as cells age 14 , 46 . Many of the proteins we found increased in young cells were lysosomal and cell surface proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas female CD-1 mice require 2–3-fold more morphine for an equivalent analgesic response to males, the difference is abolished in T-cell deficient mice (Rosen et al, 2019). Female rodents have greater abundance of macrophages in peritoneal and pleural cavities, higher TLR expression by resident macrophages and greater production of pro-inflammatory cytokines on macrophage stimulation (Scotland et al, 2011; Ćuruvija et al, 2017). These findings support the view that further investigation into the role of macrophages in chronic pain conditions affecting women is warranted.…”
Section: Macrophages and Regulation Of Nociceptive Signalingmentioning
confidence: 99%
“…Related to this concept, hormone treatment stimulated NO release in human peripheral monocytes and in a murine macrophage cell line via GPER activation coupled with intracellular calcium influx (54, 55). In line with this, stimulation with LPS in isolated peritoneal macrophages from young female rats resulted in elevated NO release; this effect was not observed in macrophages derived from the middle-aged animals, where circulating E2 levels were diminished (56). Moreover, macrophages produce and use arachidonic acid and its different metabolites for the recognition of pathogens and to enhance or suppress inflammatory response (57).…”
Section: Estrogen Effects On Immune System Cellsmentioning
confidence: 71%
“…The modulation of this chemokine impacts not only the macrophage's function but also the neutrophil's recruitment to inflammation sites, mediating pathogen clearance (66). E2 can also modulate other functional macrophage cytokines; its treatment decreased IL-6, TNF-α, and IL-1β expression in whole blood cultures derived from healthy postmenopausal women, in bone marrow cell cultures, and in ex vivo rat macrophages (56, 6770). The modulation of these cytokines was confirmed to be an E2-dependent effect, according to the opposite event found in these cells when they were treated with ICI 182,780 (69).…”
Section: Estrogen Effects On Immune System Cellsmentioning
confidence: 99%